In the face of epistemic injustices?: on the meaning of people-led war crimes tribunals. (August 2015) - Boyle, Mark; Kobayashi, Audrey
This paper seeks to render intelligible the meaning of the vibrant tradition of people-led war crimes tribunals (PWCTs) which has emerged in the past half a century. Drawing upon recent postcolonial critiques of extant literature on geographies of care and responsibility, and informed by Third World Approaches to International Law (TWAIL), we question the capacity of the international legal system to provide justice for 'others' (especially subaltern and colonised communities) at a distance. We situate PWCTs in the context of the claim that the international legal system is systemically contaminated because it is conceptually Western. We interrogate the seminal Russell Tribunal on Vietnam (1966–67) and in so doing are led to place under scrutiny the postcolonial and dialectical ethics which characterised the work of French philosopher, literary giant, and political activist Jean-Paul Sartre before, during, and after his tenure as Executive President of this tribunal. We argue that insofar as PWCTs speak subaltern truth to power, they work to decentre the Western ethical, legal, and juridical canon and confront insidious epistemic injustices. We conclude that any search for a postcolonial ethics to guide caring from afar can both inform and be informed by PWCTs.